Diversity of Ferns (Pteridophyta) as an Indicator of Environmental Sustainability in Fogi Village, Sula Islands Regency - Nursina Banapon; Siti Nurjannah; Ramli Hadun; Adriani Adriani; Reyna Ashari; Laswi Irmayanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Ferns (Pteridophyta) are spore-reproducing vascular plants important in tropical forest ecosystems, and Indonesia is a global center of their diversity with over 2,000 species. However, fern diversity in North Maluku is still poorly documented. This study aimed to analyze the species composition and diversity of ferns as well as their implications for environmental sustainability in Fogi Village, Sanana District, Sula Islands Regency. The study was conducted across four habitat types: home garden, residential, riverbank, and mixed plantation, using purposive sampling with line transects of 1 km length and 10 m width. Data analysis included the Shannon-Wiener diversity index (H'), Margalef species richness index (Dmg), and species evenness index (E), complemented by a descriptive-ecological assessment to discuss implications for the sustainability of the local ecosystem. A total of 10 fern species were recorded comprising 229 individuals. The dominant species across habitat types were Pteris tripartita in home garden habitat (9 individuals) and Selaginella sp. in residential (15), riverbank (12), and mixed plantation (17) habitats. The residential habitat recorded the highest values of species diversity (H') and species richness (Dmg) compared to other habitat types. Species evenness (E) approached 1 across all habitats, indicating a relatively balanced distribution of fern species. Ecologically, the Fogi Village area retains potential to sustain its ecosystem functions; however, the low species richness recorded across all habitat types warrants attention in efforts toward sustainable environmental management of the area. In conclusion, the fern community at the research site shows a moderate level of diversity with a relatively even distribution of species across various habitat types. The high uniformity in all habitats indicates the absence of extreme dominance by a single species.